99.1k views
2 votes
Simplify the expressions by combining like terms

1. 6n^2 - 2n - 3 + 5n^2 - 9n - 6
2. 8c^2 - c + 3 + 2c^2-c + 2

User AngryDuck
by
6.0k points

2 Answers

2 votes

Answer:

1. 11n^2-11n-9

2. 10c^2-2c+5

Explanation:

1. 6n^2+5n^2 = 11n^2

-2n-9n = -11n

-3-6=-9

2. 8c^2+2c^2 = 10c^2

-c-c= -2c

3+2=5

User Rejo
by
5.6k points
2 votes

Hey!

---------------------------------------------------------

Question #1:

= 6n^2 - 2n - 3 + 5n^2 - 9n - 6

= 6n^2 + (-2n) + (-3) + 5n^2 + (-9n) + (-6)

= (6n^2 + 5n^2) + (-2n + -9n) + (-3 + -6)

= (11n^2) + (-11n) + (-9)

Answer: 11n² + (-11n) + (-9)

---------------------------------------------------------

Question #2:

= 8c^2 - c + 3 + 2c^2 - c + 2

= 8c^2 + (-c) + 3 + 2c^2 + (-c) + 2

= (8c^2 + 2c^2) + (-c + -c) + (3 + 2)

= (10c^2) + (-2c) + (5)

Answer: 10c² + (-2c) + 5

---------------------------------------------------------

Hope This Helped! Good Luck!

User Rahly
by
6.3k points